The love poems of John Donne. - Armistead, J. M. (Knoxville : Dept. of Television Services, University of Tennessee, 1979)
SUMMARY: A lecture by Dr. Armistead on John Donn's poetry.
DVD.
Copied from U-matic.
Keywords: Donne, John, -- 1572-1631 -- Criticism and interpretation